Polyamines modulate the roscovitine-induced cell death switch decision autophagy vs. apoptosis in MCF-7 and MDA-MB-231 breast cancer cells - Akyüz, Kaan Gencer; Kerman, Ezgi Melek; Çoker Gürkan, Ajda; Palavan Ünsal, Zeynep Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Spandidos Publ Ltd, Pob 18179, Athens, 116 10, Greece, 2015)
Current clinical strategies against breast cancer mainly involve the use of anti-hormonal agents to decrease estrogen production; however, development of resistance is a major problem. The resistance phenotype depends on the modulation of cell-cycle regulatory proteins, cyclins and cyclin-dependent kinases. Roscovitine, a selective inhibitor of cyclin-dependent kinases, shows high therapeutic potential by causing cell-cycle arrest in various cancer types. Autophagy is a type of cell death characterized by the enzymatic degradation of macromolecules and organelles in double- or multi-membrane autophagic vesicles. This process has important physiological functions, including the degradation of misfolded proteins and organelle turnover. Recently, the switch between autophagy and apoptosis has been proposed to constitute an important regulator of cell death in response to chemotherapeutic drugs. The process is regulated by several proteins, such as the proteins of the Atg family, essential for the initial formation of the autophagosome, and PI3K, important at the early stages of autophagic vesicle formation. Polyamines (PAs) are small aliphatic amines that play major roles in a number of eukaryotic processes, including cell proliferation. The PA levels are regulated by ornithine decarboxylase (ODC), the rate-limiting enzyme in PA biosynthesis. In this study, we aimed to investigate the role of PAs in roscovitine-induced autophagic/apoptotic cell death in estrogen receptor-positive MCF-7 and estrogen receptor-negative MDA-MB-231 breast cancer cells. We show that MDA-MB-231 cells are more resistant to roscovitine than MCF-7 cells. This difference was related to the regulation of autophagic key molecules in MDA-MB-231 cells. In addition, we found that exogenous PAs have a role in the cell death decision between roscovitine-induced apoptosis or autophagy in MCF-7 and MDA-MB-231 breast cancer cells.
Keywords: Breast cancer; Polyamines; Roscovitine; Apoptosis; Autophagy